Harley-Davidson : chasing a new generation of customers - Roese, Neal J.; Compella, Mohan ([London] : SAGE, 2016)
Although Harley-Davidson had a record sales year in 2006 - and had maintained a commanding share of the heavyweight motorcycle market for the previous decade - it had become obvious that the company needed to take new action to sustain its growth. This study examines Harley-Davidson's drive to find a new generation of riders and a more diverse customer base.
Originally Published in: Roese, N. J., & Compella, M. (2013). Harley-Davidson: Chasing a New Generation of Customers. 5-113-010. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on online resource; title from home page (viewed on April 28, 2016).
Keywords: elektronické knihy; electronic books; Harley-Davidson Incorporated; Branding (Marketing) -- Case studies; Brand name products -- Case studies